Energy expenditure of free-living reindeer estimated by the doubly labelled water method - Gotaas, Geir; Milne, Eric; Haggarty, Paul; Tyler, Nicholas J.C. (Rangifer, 2000)
The doubly labelled water (DLW) method was used to measure total energy expenditure (TEE) in three male reindeer (Rangifer tarandus tarandus) aged 22 months in winter (February) while the animals were living unrestricted at natural mountain pasture in northern Norway (69°20'N). The concentrations of 2H and l8O were measured in water extracted from samples of faeces collecred from the animals 0.4 and 11.2 days after injection of the isotopes. Calculated rates of water flux and CO2-production were adjusted to compensate for estimated losses of 2H in faecal solids and in methane produced by microbial fermentation of forage in the rumen. The mean specific TEE in the three animals was 3.057 W.kg-1 (range 2.436 - 3.728 W.kg1). This value is 64% higher than TEE measured by the DLW method in four captive, non-pregnant adult female reindeer in winter and probably mainly reflects higher levels of locomotor activity in the free-living animals. Previous estimates of TEE in free-living Rangifer in winter based on factorial models range from 3.038 W.kg-1 in female woodland caribou (R. t. caribou) to 1.813 W.kg-1 in female Svalbard reindeer (R. t. platyrhynchus). Thus, it seems that existing factorial models are unlikely to overestimate TEE in reindeer/caribou: they may, instead, be unduly conservative. While the present study serves as a general validation of the factorial approach, we suggest that the route to progress in the understanding of field energetics in wild ungulates is via application of the DLW method.